Analisis Perbandingan Daya Output Turbin Angin Tipe Vertikal (Generator 300 W) dan Panel Surya (Monokristalin 200 Wp) - Lucky Gunawan; Dian Budhi Santoso (Peneliti.net, 2022)
Electricity is one of the main needs needed by humans today. Almost all tools used by humans require electrical energy. In Indonesia, the public has not yet fully received sufficient electricity, according to the Central Statistics Agency in December 2020, the electrification ratio was 99.20%. That means that there are still around 0.80% of areas in Indonesia that do not have electricity. The purpose of this study is to analyze the comparison of the power generated by a 200 Wp solar panel with a vertical 300 watt wind turbine. The results of the study can be used in determining an independent alternative power plant for residential homes. From the measurement results, the total value of the largest solar panel electricity production reached 747,992 wh. While the average wind turbine only gets 0.26 Watt. Solar panels can be used as an option in determining alternative independent power plants for residential homes because they can produce electrical energy stably